2009
DOI: 10.1088/0004-637x/696/1/143
|View full text |Cite
|
Sign up to set email alerts
|

The Different Evolution of Gas and Dust in Disks Around Sun-Like and Cool Stars

Abstract: Planet formation is profoundly impacted by the properties of protoplanetary disks and their central star. However, how disk properties vary with stellar parameters remain poorly known. Here we present the first comprehensive, comparative Spitzer/IRS study of the dust and gas properties of disks around young sun-like stars (K1-M5) and cool stars/brown dwarfs (M5-M9). The comparison of these two large samples of over 60 sources reveal major differences in the evolution of both the dust and gas components.We repo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
191
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 185 publications
(215 citation statements)
references
References 72 publications
22
191
2
Order By: Relevance
“…Many observations have demonstrated that disk properties, such as the accretion rate and dust processing speed, depend on their host stellar properties like the effective temperature (T eff ) and mass (Muzerolle et al 2005;Herczeg et al 2009;Pascucci et al 2009;Riaz et al 2009). Correlation analysis is therefore very common in disk studies, although the derivation of both disk and stellar properties always depends on model assumptions.…”
Section: Dependence On the Stellar Propertiesmentioning
confidence: 99%
“…Many observations have demonstrated that disk properties, such as the accretion rate and dust processing speed, depend on their host stellar properties like the effective temperature (T eff ) and mass (Muzerolle et al 2005;Herczeg et al 2009;Pascucci et al 2009;Riaz et al 2009). Correlation analysis is therefore very common in disk studies, although the derivation of both disk and stellar properties always depends on model assumptions.…”
Section: Dependence On the Stellar Propertiesmentioning
confidence: 99%
“…The inventory of molecular species detected in T Tauri sources in the infrared includes: CO (e.g. Najita et al 2003), OH and H 2 O (e.g., Carr et al 2004;Salyk et al 2008), HCN and C 2 H 2 (e.g., Carr & Najita 2008, 2011Pascucci et al 2009;Mandell et al 2012) and, finally CO 2 (Pontoppidan et al 2010). Are Herbig sources also different from T Tauri sources at far-IR wavelengths?…”
Section: Introductionmentioning
confidence: 99%
“…Even in dense cores, not all nitrogen appears to have been transformed to molecular form (Maret et al 2006;Daranlot et al 2012). Observations of HCN in the surface layers of protoplanetary disks suggest that the nitrogen chemistry is strongly affected by whether or not a star has sufficiently hard UV radiation to photodissociate N 2 (Pascucci et al 2009). Thus, not only the absolute photodissociation rate but also its wavelength dependence is relevant.…”
Section: Introductionmentioning
confidence: 99%